Newborns with lower levels of circulating polyunsaturated fatty acids (PUFA) are abdominally more adipose. Issue 3 (5th December 2013) - Sanz, N.; Diaz, M.; López‐Bermejo, A.; Sierra, C.; Fernández, A.; de Zegher, F.; Ibáñez, L.
Summary Background Maternal nutrition is the main source of Poly‐Unsaturated Fatty Acids (PUFA) for the fetus. PUFA may influence the accumulation of fat in early life. Objectives & Methods In 33 breastfed infants born appropriate‐for‐gestational‐age, we studied whether body composition (judged by absorptiometry at 2 wk and 4 mo) relates to PUFA levels (assessed by gas chromatography) in the maternal or fetal circulation at birth. Results Abdominal fat at 2 wk associated negatively to umbilical‐cord levels of separate PUFA (linoleic, arachidonic, eicosapentanoic and docosahexaenoic acid; all P between 0.001 and 0.015). Collectively, the assessed n‐6 PUFA on one hand and the n‐3 PUFA on the other hand associated negatively to the absolute amount of abdominal fat (in grams; P = 0.001 and P = 0.002, respectively) and to the relative amount of abdominal fat (fraction of total fat; P = 0.001 and P = 0.006, respectively). No other significant associations were observed. Conclusion In conclusion, newborns with lower levels of circulating PUFA were found to be abdominally more adipose. The mechanisms underpinning these associations remain to be determined.